Analisis Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil Dan Menengah Dalam Penyusunan Laporan Keuangan UMKM Aceh Hidroponik Kecamatan Karang Baru Kabupaten Aceh Tamiang - Muhammad Al Giffary; Nurlaila Nurlaila; Khairina Tambunan (Journal Economic Excellence Ibnu Sina, 2023)
The purpose of this study was to analyze the suitability of financial statement reports based on the application of accounting based on SAK EMKM at Umkm Aceh Hidroponik Medang Ara Village, Karang Baru District, Aceh Tamiang Regency. This research was conducted using a qualitative method with a descriptive approach and the application of recording financial statements based on SAK EMKM using primary and secondary data taken from Umkm Aceh Hidroponik. The data collection technique in this study uses interview and documentation techniques and the analysis technique used is using data reduction, data presentation and conclusion drawing. Based on data analysis, the results showed that Umkm Aceh Hidroponik has implemented accounting but the recording of financial statements carried out is still manual and very simple and its application has not followed the provisions in SAK EMKM. The financial statements prepared by Umkm Aceh Hidroponik are only in the form of an income statement while the statement of financial position and notes to the financial statements do not exist. The obstacle that causes Umkm Aceh Hydroponics not to be implemented is that they do not know and understand the preparation of business financial reports based on the Micro, Small, Medium Entity Financial Accounting Standards (SAK EMKM).